Strategic Lessons from Built-to-Suit and Construction Negotiations in Brazil - Alisson Oliveira Gadelha , Alisson Oliveira Gadelha; Murillo de Oliveira Dias, Murillo de Oliveira Dias (IPHO-Journal of Advance Research in Science And Engineering, 2026)
The research investigates how two separate negotiations occur in Brazil for Built-to-Suit (BTS) lease agreements and construction administration contracts. Three organizations held separate talks that involved multiple changes to their projects, contract disputes, and interruptions from various stakeholders. The conflict between parties evolved into collaborative work through their combined efforts to establish trust, their commitment to transparency, and their use of integrative strategies. The project resulted in obtaining a BTS contract that included shared facilities and a construction administration agreement, achieved through the critical meeting. The research findings demonstrate that effective governance systems, along with flexible negotiation techniques and proper stakeholder management, are essential for successful high-pressure negotiations, providing valuable insights for business leaders and academics working in the real estate and construction sectors.